Dermatomyositis following resection of thyroid and breast cancer: a case report and literature review - Yang, Miaomiao; Liu, Jiannan (Frontiers in Oncology, 2025)
BackgroundDermatomyositis is an idiopathic inflammatory myopathy and occurs as a paraneoplastic syndrome. Here, we report an unusual case of dermatomyositis that developed in a patient after the resection of thyroid cancer and breast cancer. The intercorrelation between dermatomyositis and neoplastic disorders was discussed.Case presentationA 60-year-old female farmer was diagnosed with thyroid cancer and breast cancer and then developed dermatomyositis after two curative surgeries and adjuvant chemotherapy. Dermatomyositic symptoms occurred after the fifth cycle of adjuvant chemotherapy for breast cancer and deteriorated progressively. Case history, imaging, and laboratory data were reviewed. This patient subsequently received systemic immunosuppressant therapy and thus dermatomyositis gradually resolved.ConclusionsA combination of thyroid cancer and breast cancer is thought to be very rare, especially in patients who develop dermatomyositis after thyroidectomy and mastectomy. An extraordinary case was reported in this study. Potential mechanisms for the development of dermatomyositis and novel insights neoplastic autoimmune diseases were proposed.